Urban sustainability transitions in China: a systematic analysis of the diffusion of sponge city policy - Qian, Chen; Lyu, Shupeng (Frontiers in Environmental Science, 2026)
As a new generation of urban water management concepts, sponge city (SC) initiative proposed by China plays the pivotal role in mitigating flood risk, combating climate change, and enhancing environmental resilience. The diffusion patterns and mechanisms of SC policy are analyzed based on the panel data of 263 cities from 2015 to 2020. The results show that the diffusion of SC policy follows an S-shaped curve temporally and involves three distinct stages: local diffusion stage (2015), comprehensive diffusion stage (2016–2018), and saturation diffusion stage (2019–2020). Spatially, the SC policy has diffused predominantly from pilot cities to non-pilot cities and from sub-provincial cities and provincial capitals to ordinary prefecture-level cities, indicating significant neighborhood and demonstration effects. Furthermore, bureaucratic accountability and officials’ promotion incentives are key drivers of the diffusion of SC policy. Specifically, a one-unit increase in vertical pressure from the central government, vertical pressure from the provincial government, horizontal pressure, or mayor’s age is associated with 7.768, 4.697, 3.074, and 1.039 times higher odds of policy adoption by a prefecture-level city, respectively. Compared to the first year in office, the odds of policy adoption by a prefecture-level city are 1.485 and 1.74 times higher in a mayor’s second and third year in office, respectively. However, no comparable association is observed for municipal party secretaries. These findings enrich the theoretical landscape of policy diffusion studies. They further provide critical insights for formulating climate adaptation strategies and advancing sustainable urban transformation in unitary states and multi-tier administrative systems.